(untitled) (Orfeu, 2024)
In this article, we aim to discuss the configuration of musical labor in contemporary times, particularly focusing on performers and composers. Through the investigation of the problematic notion of the multitasking musician – one who consolidates various roles previously undertaken by other professionals in the production chain – we seek to explore the interplay between dimensions of work, information, technology, and time. Drawing upon two interviews conducted in the light of scientific literature, historical nuances of a labor undergoing profound transformation or adaptation were observed. The recurring waves of productive restructuring, catalyzed since the 1970s on a global scale, seem to have instigated a sharp shift in the ways music is produced, distributed, and commercialized over the past 20 years. Present working conditions appear to paint a bleak picture for those reliant on their music for livelihood, as suggested by the interviews.